Sustainable Healthy Diets through Food Systems Transformation (SHiFT) in Vietnam - Huynh Thi Thanh Tuyen (Bioversity International and the International Center for Tropical Agriculture, 2022)
To achieve its mission of delivering science and innovation that advance transformation of food, land, and water systems in a climate crisis, CGIAR has launched a new portfolio of Initiatives. Vietnam is one of the priority countries of CGIAR with nine initiatives to be implemented in the country. Among the nine initiatives, SHiFT is the only CGIAR initiative with the primary focus on ensuring sustainable healthy diets for all through food systems transformation.